Teachers’ Role in Developing Indonesian Students’ Character Education at School - Gusti Ayu Made Trisna Yanti (English Education Department STKIP Agama Hindu Singaraja, 2021)
Character education as one of important lesson should be learned by students. It is important in order to build a good behavior of students. Moreover, it also important because the quality of a nation can be seen from the quality of the citizen. The more educated a person is, the more advanced the intelligence of nation. However, there were lot of students who still do unwanted thing at school which categorized as bad attitude. Unwanted activities may happen because students were lack of character education. Therefore, this study aimed to describe theoretical concept of teacher’s role in order to develop character education at school. Teacher’s role in developing character education is very important due to most of students’ time they spend at school. There were two main roles and several addition roles which can be taken by the teacher in order to teach character education and build a good character of students